Catalpol alleviates the lipopolysaccharide-induced inflammatory response of BV2 cells - Sijie Liu; Jiayi Zhu; Hao Huang; Jiaxiang Xu; Biao Zhang; Yi Luo (Bangladesh Journal of Pharmacology)
This study aimed to investigate the effect of catalpol on the inflammatory response of murine microglial cell line (BV2 cells) induced by lipopolysaccharide. Cell proliferation activity was detected by CCK-8 assay. The morphology of BV2 was observed by an optical microscope. The inflammatory factors interleukin-1β (IL-1β), IL-6, and tumor necrosis factor-α (TNF-α) were detected by enzyme‐linked immunosorbent assay (ELISA). Reactive oxygen species (ROS) were detected by flow cytometry. Induced nitric oxide synthase (iNOS) level was detected by immunofluorescence. The results showed that 5 μg/mL catalpol did not effect the proliferation of BV2 cells, while 10 μg/mL catalpol significantly decreased the viability of BV2 cells. Then the experiment was carried out with 5 μg/mL catalpol. Catalpol can improve the morphology of lipopolysaccharide-induced BV2 cells, decrease the level of inflammatory factors, and reduce the production of iNOS and ROS. Therefore, catalpol can inhibit the lipopolysaccharide-induced activation of BV2 cells and has anti-inflammatory effects.